Is the use of antidepressants associated with patient-reported outcomes following total hip replacement surgery? - Greene, Meridith E (Acta Orthop, 2016)
BACKGROUND AND PURPOSE: Patients with anxiety and/or depression tend to report less pain reduction and less satisfaction with surgical treatment. We hypothesized that the use of antidepressants would be correlated to patient-reported outcomes (PROs) 1 year after total hip replacement (THR), where increased dosage or discontinuation would be associated with worse outcomes. PATIENTS AND METHODS: THR cases with pre- and postoperative patient-reported outcome measures (PROMs) were selected from the Swedish Hip Arthroplasty Register (n = 9,092; women: n = 5,106). The PROMs were EQ-5D, visual analog scale (VAS) for pain, Charnley class, and VAS for satisfaction after surgery. These cases were merged with a national database of prescription purchases to determine the prevalence of antidepressant purchases. Regression analyses were performed where PROs were dependent variables and sex, age, Charnley class, preoperative pain, preoperative health-related quality of life (HRQoL), patient-reported anxiety/depression, and antidepressant use were independent variables. RESULTS: Antidepressants were used by 10% of the cases (n = 943). Patients using antidepressants had poorer HRQoL and higher levels of pain before and after surgery and they experienced less satisfaction. Preoperative antidepressant use was independently associated with PROs 1 year after THR regardless of patient-reported anxiety/depression. INTERPRETATION: Antidepressant usage before surgery was associated with reduced PROs after THR. Cases at risk of poorer outcomes may be identified through review of the patient’s medical record. Clinicians are encouraged to screen for antidepressant use preoperatively, because their use may be associated with PROs after THR.